ANALYSIS OF FOOD EXPENDITURES BY GAMBIR-FARMING HOUSEHOLDS IN HARAU SUBDISTRICT - Ratna Agustia; Nin Patri Enanti; Yuliatri; Sulastri; Fefriyanti; Rita Erlinda (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract:  This study aims to examine the food consumption expenditures of gambir-farming households in Harau Subdistrict. The research was conducted in that area, specifically in the village of Harau, with locations selected through purposive sampling. The research design employed was a survey. The research sample consisted of farmers cultivating gambir plants in Harau Subdistrict, with a total of 30 respondents representing the population. A quantitative analysis approach was used to describe the magnitude of household food consumption expenditures among gambir farmers in Harau Village, Lima Puluh Kota Regency. The results of the study indicate that total food consumption expenditures amount to Rp2,283,583 per month or Rp27,403,000 per year. The largest expenditure component comes from the consumption of side dishes or animal-based foods, amounting to Rp756,667 per month or Rp9,080,000 per year.   Keywords:  Consumption; Expenditure; Households; Farmers; Gambir   Abstrak: Penelitian ini bertujuan untuk mengkaji pengeluaran konsumsi pangan rumah tangga petani gambir di Kecamatan Harau. Kegiatan penelitian dilaksanakan di wilayah tersebut, tepatnya di Kenagarian Harau, dengan pemilihan lokasi yang dilakukan secara sengaja (purposive). Jenis penelitian yang digunakan adalah survei. Sampel penelitian terdiri dari petani yang membudidayakan tanaman gambir di Kecamatan Harau, dengan jumlah responden sebanyak 30 orang yang mewakili populasi. Pendekatan yang digunakan adalah analisis kuantitatif untuk menggambarkan besarnya pengeluaran konsumsi pangan rumah tangga petani gambir di Nagari Harau, Kabupaten Lima Puluh Kota. Hasil penelitian menunjukkan bahwa total pengeluaran konsumsi pangan mencapai Rp2.283.583 per bulan atau Rp27.403.000 per tahun. Komponen pengeluaran terbesar berasal dari konsumsi lauk atau pangan hewani, yaitu sebesar Rp756.667 per bulan atau Rp9.080.000 per tahun.   Kata Kunci: Konsumsi; Pengeluaran; Rumah Tangga; Petani; Gambir